Illness representation of COVID-19 affected public’s support and anticipated panic regarding the living with the virus policy: a cross-sectional study in a Chinese general population - Yu, Yanqiu; Ling, Rachel Hau Yin; Ng, Joyce Hoi-Yuk; Lau, Mason M. C.; Ip, Tsun Kwan Mary; Lau, Joseph T. F. (Frontiers in Public Health, 2023)
Background There is a global trend for countries to adopt the Living with the Virus (LWV) policy regarding COVID-19. Little is known about the public’s supportiveness and emotional responses (e.g., anticipated panic) related to this policy. Such responses may be associated with illness representations of COVID-19 (i.e., how people think and feel about COVID-19). This novel topic was investigated in this study to facilitate policy-making and health communication. Methods A random, population-based telephone survey interviewed 500 adults aged ≥18 of the Hong Kong general adult population from March to April 2022. Results The prevalence of the public’s support and anticipated panic regarding the LWV policy, which were negatively correlated with each other, was 39.6 and 24.2%, respectively. The illness representation constructs of consequences, timeline, identity, illness concern, and emotional representations were negatively associated with supportiveness and positively associated with anticipated panic regarding the LWV policy. Illness coherence was significantly associated with policy support but not with anticipated panic. The associations between personal control/treatment control and supportiveness/anticipated panic were statistically non-significant. Moderation analyses showed that the above significant associations were invariant between those with and without previous COVID-19 infection. Conclusion Policymakers need to be sensitized about the public’s supportive/unsupportive attitude and potential worry (panic) when adopting the LWV policy. Such attitudes/emotional responses may be affected by people’s illness representations of COVID-19. In general, those who found COVID-19 involving a milder nature and less negative emotions would be more supportive and anticipated less panic under the LWV policy.